The correct answer is X=-2.
First remove the parentheses and factor out 2.
1/2•(2-6x)-4(x+3/2)=-(x-3)+4 turns into
1/2•2(1-3x)-4(x+3/2)=-(x-3)+4.
Then distribute -4 through the parentheses,
1/2•2(1-3x)-4x-6=-(x-3)+4
Then change the sign of the x-3 to x+3,
1/2•2(1-3x)-4x-6=-x+3+4
Then reduce the numbers with the greatest common factor which is 2,
and remove unnecessary parentheses,
1-3x-4x-6=-x+7
Then calculate the differences and collect like terms,
-5-7x=-x+7
Then move the variable to the left side and change its sign, and move the constant to the right hand side and change its sign,
-7x+x=7+5
Then add and collect the like terms,
-6x=12
And finally divide both sides by -6 to get X=-2.
Whew lol
B) 7 would make it true, since both 42/54 and 7/9= 0.77 repeating
Answer:
Step-by-step explanation:
We have to find profit .
This can be easily found using a formula for Profit given the Revenue and Cost.
Given that:
to find P(x) we can simply subtract R(x) by C(x).
and finally, after simplify this equation subtracting 6x by 2.3x.
this is the equation for the profit
Answer:
(22) = 7
Step-by-step explanation:
The inverse function maps the output of the function back to its input
f(7) = 22 means when input is 7 the output is 22
The inverse maps the output 22 back to the input 7 , that is
(22) = 7
Answer:
The rate would be: 4:20 and the unit rate would be 1:5.
Step-by-step explanation: